Rheumatic Fever & Rheumatic Heart Disease: Azithromycin Must Replace Penicillin for Treatment and Prophylaxis - Lalchandani, Arati; Raj, Senthi; Godara, M.; Singh, V.; Kumar, A.; Rajan, A. (Journal of Nepalgunj Medical College, 2016)
The standard and age-old treatment of RF/ RHD is a single injection of Benzathine Penicillin G given intramuscular after sensitivity test in a dose of 1.2 million units. For secondary prophylaxis, this is followed by Injection Benzathine Penicillin given intramuscular, each time after sensitivity test, after every 21 days (3weeks), in the same dose of 1.2 million units. The treatment and prophylaxis of RF/ RHD has never seriously been reviewed in the light of newer drugs discovered for GAS (Group A Streptococcus) after Penicillin. All the other drugs mentioned above are oral forms which could never be an alternative to Benzathine Penicillin due to the daily dose required, except for Azithromycin which has a long half-life and several other pharmacological properties which make it an ideal drug for treatment and prophylaxis of RF/ RHD. Benzathine Penicillin G is in use for past 60 years due to convenience of dosing, its undoubted efficacy in eradication of the GABHS, and the low cost. But the scene is changed now. JNGMC Vol. 12 No. 2 December 2014, Page: 42-45